Method for Indirect Quantification of CH4 Production via H2O Production Using Hydrogenotrophic Methanogens - Taubner, Ruth-Sophie; Rittmann, Simon K.-M. R. (Frontiers in Microbiology, 2016)
ydrogenotrophic methanogens are an intriguing group of microorganisms from the domain Archaea. They exhibit extraordinary ecological, biochemical, physiological characteristics yellowand have a huge biotechnological potential. Yet, the only possibility to assess the methane (CH_4) production potential of hydrogenotrophic methanogens is to apply gas chromatographic quantification of CH_4. In order to be able to effectively screen pure cultures of hydrogenotrophic methanogens regarding their CH_4 production potential we developed a novel method for indirect quantification of yellowthe volumetric CH_4 production rate by measuring yellowthe volumetric water production rate. This yellow method was established in serum bottles for cultivation of methanogens in closed batch cultivation mode. Water production was yellowestimated by determining the difference in mass increase in an isobaric setting. This novel CH_4 quantification method is an accurate and precise analytical technique, yellowwhich can be used to rapidly screen pure cultures of methanogens regarding yellowtheir volumetric CH_4 evolution rate. yellowIt is a cost effective alternative yellowdetermining CH_4 production of methanogens over CH_4 quantification by using gas chromatography, especially if yellow applied as a high throughput quantification method. yellowEventually, the method can be universally applied for quantification of CH_4 production from psychrophilic, thermophilic and hyperthermophilic hydrogenotrophic methanogens.